Animation vs. Simulation - Tong, Togan; Aydin, Erdal Devrim; Pusat, S. Emre (ECAADE-EDUCATION & RESEARCH COMPUTER AIDED ARCHITECTURAL DESIGN EUROPE, 2009)
In his book Cinema as an Art, Rudolf Arnheim states that cinema (art) cannot achieve to realize the mechanical reproduction of the real (nature) because of technical limitations but also states that these limitations are compulsory for the production of art. According to Arnheim, these limitations cause artists to interpret the real (nature) and to materialize impressive expressions. Architecture presents its productions to its viewers (customers) using some kind of media, before materializing them in the physical world. The most common ones nowadays are technical drawings (perspectives), models, photographs and computer aided models and animations. The architect makes impressive expressions based on the technical limitations of the medium he/she uses. With the computer technology, simulation gives possibilities to the architect for presenting and experiencing his/her art very close to reality. Simulation is the best way to reproduce the reality mechanically, when it is compared to other mediums. In this study, simulation's potential as an architectural presentation technique is examined through Arnheim's vision and Rembrandt's painting Staalmeesters.
Keywords: Simulation; animation; architectural presentation; interactivity; Architecture